2021
DOI: 10.1177/21925682211031190
|View full text |Cite
|
Sign up to set email alerts
|

Direct Cost of Illness for Spinal Cord Injury: A Systematic Review

Abstract: Study Design: Systematic review. Objective: Providing a comprehensive review of spinal cord injury cost of illness studies to assist health-service planning. Methods: We conducted a systematic review of the literature published from Jan. 1990 to Nov. 2020 via Pubmed, EMBASE, and NHS Economic Evaluation Database. Our primary outcomes were overall direct health care costs of SCI during acute care, inpatient rehabilitation, within the first year post-injury, and in the ensuing years. Results: Through a 2-phase sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…In a first assessment of the neutrophil proteome, a total of 251 major cellular proteins in different compartments were identified by gel-LC-MS/MS [ 88 ]. This proteome included the azurophilic granule proteins NE and MPO as well as PAD4, which catalyzes the deimination of arginine to citrulline and mediates chromatin decondensation [ 89 , 90 , 55 ]. In a recent proteome analysis by Petretto et al, 330 NET-associated proteins were identified; many with posttranslational modifications [ 91 ].…”
Section: The Composition Of Netsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a first assessment of the neutrophil proteome, a total of 251 major cellular proteins in different compartments were identified by gel-LC-MS/MS [ 88 ]. This proteome included the azurophilic granule proteins NE and MPO as well as PAD4, which catalyzes the deimination of arginine to citrulline and mediates chromatin decondensation [ 89 , 90 , 55 ]. In a recent proteome analysis by Petretto et al, 330 NET-associated proteins were identified; many with posttranslational modifications [ 91 ].…”
Section: The Composition Of Netsmentioning
confidence: 99%
“…Traumatic spinal cord injury (tSCI) can result in permanent paralysis of patients. Beside individual sequelae and psychosocial trauma, the socioeconomic burden is substantial [ 89 ]. A recent multicenter cohort study showed that tSCI patients are among the most resource intense patient group of $11.193 per admission in Canada [ 247 ].…”
Section: Perspectivementioning
confidence: 99%
“…Many studies have also shown that SCI patients are more likely to suffer from depression or anxiety than normal people [5][6][7]. Additionally, the financial cost per SCI patient is generally higher [8]. It is evident that SCI can place a serious burden on the patient physically, psychologically, and financially.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the annual national cost in 2009 was as high as $1,7 billion [3], and for each patient ranged from $30,770 to $62,563 in 2016 [4]. The most significant cost derived from the severity of disability and complications developed during the hospitalization such as pressure ulcers and infections [5]. The SCI burden is extended also to the psychology of the younger patients, suddenly experiencing paraplegia or quadriplegia [6,7].…”
Section: Introductionmentioning
confidence: 99%